Expedient preparative isolation, quantification and characterization of limonoids from neem fruits - Haldar, Saikat; Phapale, Prasad B.; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Analytical Methods, 2013)
Major basic limonoids from Neem fruits such as azadirone, epoxyazadiradione and azadiradione were isolated in preparative scale using an automated and rapid medium pressure liquid chromatography (MPLC)-based protocol. They were individually quantified using HPLC. An LC-ESI-MS/MS-based rapid identification technique was developed for the high-throughput screening of these limonoids in phytochemical extracts.